3 Safe timely persone centerd care – step. (3rd November 2019) - Braitberg, George
Abstract : Our organisation noted a reduction in performance in our patient experience survey Results and realised that our clinical governance framework needed to be refreshed and refocus the organisation towards patient centred care. Projects and work that were planned or already underway were mapped back to the framework, which we called STEP- Safe, Timely Person Effective Person centred care. Existing scorecards, polices and procedures were changed. Position descriptions, onboarding processes and performance appraisals were all rewritten to ensure our staff understood the elements of our new clinical governance framework. STEP was the result of our five clinical governance domains; leadership and culture, consumer participation, risk management, clinical practice and our workforce. Early projects that were initiated under STEP included the development of a 'Fasting app' to prevent multiple episodes of fasting following cancellation of surgery by providing visibility on the elective surgery booking list. (Safe/Timely/Risk Management). Other initiatives included a next of kin texting initiative to update families on patient progress (Patient centred/Consumer Partnerships), implementation of multidisciplinary ward governance rounds (Effective/Clinical Practice) and participation in an online patient feedback platform (Patient centred/Consumer Partnerships). Our preexisting Safety Culture Program was 'rolled in' to our Clinical Governance Framework (Safe/Leadership and Culture). We believe this approach 'personalises' clinical governance and assists front line care givers and consumers in understanding how our organisation monitors and improves the care we provide, ensuring it is safe, timely effective and person centred.